APROPRIATION OF METAFORA IN FILM ADVERTISING “MANDIRI SECURITAS” - Handriyotopo, Handriyotopo; Lastoro, GR Lono; Gustami, SP (Capture : Jurnal Seni Media Rekam, 2018)
Mandiri Securitas Advertising Film is an advertising film using the rhetoric strategy of visual communication of the kris masters as a creative approach. The theme as a basic idea for the creation of the Mandiri Securitas advertisement film seeks to understand the effort of working hard to produce details from the master's work to produce a keris blade, created with metaphorical rhetoric to represent the image of Mandiri Securitas in serving its customers whether they can work well or not by looking at each the role of the political rhetoric domain and banking rhetoric in both. The purpose of this study was to critically identify the two domain metaphorical rhetoric by looking at each role of the constituent elements of the Mandiri SecuritasÂ  advertising film. This research method uses descriptive qualitative deconstruction by "appropriation minus one" technique through the dismantling of the banking domain and the domain of perkerisan to see the position of the filmmatic metaphorical rhetoric of the Mandiri Securitas Â advertisement. Advertising films contain constituent elements such as visual, audio, animated effects and voice over that support the formation of advertising metaphors. Through appropriation "minus one" can be found the position of visual rhetoric of the keris domain is able to deliver messages from products desired by Mandiri Securitas , but if "animated text" and "voice over" are removed, there is no rhetorical relationship in both.